Campos magnéticos y sus efectos biológicos - Sarta Fuentes, José Antonio; Bobadilla Rojas, Juan Guillermo (Ingeniería, 2003)
This paper shows a revision about researches related to the effects of the magnet fields on biological systems in order to establish the state of the art in this kind of investigations.